Estudo preliminar da expressão de marcadores moleculares no câncer de estômago ocorridos no estado do Ceará - Montenegro, Raquel Carvalho (2003)
In search for a better understanding of the biology of tumors, molecular markers related to proliferation, resistance and apoptosis have been intensively studied in the different types of cancer. These markers can help on the elucidation of more specific therapeutic targets for the treatment of various tumors. It was observed that stomach cancer is the second most frequent cause of death in the world. In Brazil, this tumor is among the five major causes of death by cancer and the adenocarcinomas are held responsible for about 95% of all cases. For that matter, the expression of KI-67, PCNA, p53, bcl-2 and c-myc were evaluated independently and in a combined form in stomach adenocarcinomas. Thus, KI-67 and PCNA were confronted in order to determine which one would pose as a better cellular proliferation marker. Finally, a DNA extraction tecnique using CTAB was implemented on tumor tissue as well as the molecular analysis of the p53 gene by SSCP. The positive results were compared with those obtained by the imonohistochemistry analysis. The tumors were collected in surgical procedure, processed and classified histopathologically. The markers were detected by the imunohistochemical method SABP. The DNA was extracted by the CTAB method and the exons 5, 7 and 8/9 of the p53 gene analyzed by SABP. Some of the samples were obtained from biopsy arquives. The age range of the patients was between 61 and 70 years, with 48,1% of the tumors presenting an intestinal origin, 40,7% were diffuse and the other 11,2% were mixed. According to the location, 50% of the tumors were found to be proximal. 41,1% of the tumors were found to be in a low stage (I – IIIA), 44,8% in a high stage (IIIB – IV) and 13,8% were not staged. The imunohistochemical results indicated that KI-67 is the best marker to estimate cellular proliferation in stomach adenocarcinomas. In an independent manner, the tumors showed an 89,3% positivity for KI-67, 62,5% for PCNA, 50% for p53, 60,7% for bcl-2 e 66,7% for c-myc. According to the staging, the difference was significant only to p53 (p = 0,02), with a 66,7% positivity to the tumors in low stage and 16,7% for the ones on a high stage. When evaluated in a combined form, the associations of KI-67+/p53- (p=0,012) (66,67%) and c-myc+/p53- (p=0,02) (63,64%) both for the high stage tumors, were found to be significant. The DNA extraction technique applied to the tumor tissue was found to be satisfactory. For the SSCP analyses, five patients had mutation on the exon 5 (3) and on the exon 7 (2). Based on that, we may conclude that KI-67 is the best marker to access the proliferation of the stomach adenocarcinomas and that there are two proliferation activation pathways: one being dependent and the other independent of the p53 gene.